Education Effect on Social Development: Intellectually and Politically Underestimated (Revista Peruana de Investigación Educativa, 2011)
Basic and advanced education is now rapidly expanding around the world, and demographic and epidemiological research literatures brim with results showing the robust positive association between educational attainment and health, plus other individual behaviors and attitudes essential for social development. This “education effect” is so pronounced that education can be assumed to be a major cause of the first demographic transition of modern society, consisting of reduced mortality and fertility, and longer life spans, which indicate a significant improvement in overall population health and development. The first demographic transition has already occurred in many nations worldwide, but for poorer nations this transition remains a crucial challenge to sustainable social development. While most demographers and health researchers acknowledge the persistent and significant association between formal schooling and positive health outcomes, why education has this influence is not well understood. With crucial policy implications hanging in the balance, there is confusion over the role of education in social development policy.
Keywords: education and social development; education and demographic transition; effect education; expansion of education